Kajian Tematis Keputusan-keputusan Majelis Tarjih Muhammadiyah tentang Perempuan - - Samsuri; Iffah Nur Hayati (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
This research aims to: (1) classify the themes of Majelis Tarjih Muhammadiyah's decisions on woman and its gender relation issues; (2)find the contribution of Majelis Tarjih Muhammadiyah's decisions as a movement of Islamic thought reformation to gender relation issues. As a descriptive-qualitative research the subject of research is all of Majelis Tarjih's decisions. Documentation technique was used to collect primary documents which have been published by Majelis Tarjih Muhammadiyah. Sufficient of references and check recheck of subject of research were used to achieve credibility this research. The Majelis Tarjih's decisions on woman classified in three groups, Le. Putusan Tarjih (Tarjih Decisions), Fatwa fatwa Agama(Fatwas on Religion Issues), and Wacana Tarjih (Tarjih's Discourses). Gender's sensitivity of Majelis Tarjih's decisions on woman changed to constructive paradigm. The contemporary approaches of Islamic studies influenced the ijtihad methods of Majelis Tarjih. Majelis Tarjih's decisions on woman has contributed positively to Islamic thought movement on gender relation in Indonesia.